Validation of the Body Shape Questionnaire (BSQ) for Colombian population (2007)
The standardization of the Body Shape Questionnaire test was performed on a typical Colombian population, consisting of a group of 1939 pre-teenager and teenager girls, aged between 9 and 19. The average age was 14, with a standard deviation of 1.83 years. The sample was randomly chosen from 7 schools (4 public and 3 private institutions), located in the city of Popayán (Cauca, Colombia). The study group was selected with the use of a stratified sampling method by.blocks, choosing the 10% of the public and private institutions from the entire population and taking the total available sample. The findings of the study show that the test is divided into two factors that have high theoretical coherence. This could be expected from a construct which refers not only to corporal dissatisfaction in general, but that is associated with corporal weight gain. In consequence, the test would not be searching for a generalized dysmorphic characteristic but for one that is associated with concern about being overweight or obese. The first-factor was called Corporal Dissatisfaction and the second, Concern about Weight. The standardization method used was construct validation through factorial analysis with Varimax rotaAon, resulting in a high differentiation between the two above mentioned factors. A KMO (Kayser Meydr Olkin) of 0.98 with a variance of 52.3% was yielded. The internal consistency was calculated by means of Cronbach alpha with intraclass correlition cofficient, yielding a measured value of 0.95 for the whole instrument, 0.95 for the first factor and 0.92 for the second factor. The scores were typified in percentiles, setting 85 as the cutting point, which is equivalent to a direct score of 59 for the Corporal Dissatisfaction factor, 54 for the Concern about Weight factor, and 112 for the general score.